A simple approach of constructing sulfur-containing porous carbon nanotubes for high-performance supercapacitors. (May 2017) - Liu, Wei; Tang, Yakun; Sun, Zhipeng; Gao, Shasha; Ma, Junhong; Liu, Lang
Abstract: Porous carbon nanotubes (PCNTs) containing sulfur were successfully fabricated through a simple approach, which is the simultaneous activation and carbonization of sulfonated polydivinylbenzene nanotubes with KOH. The PCNTs take on hierarchical porous structure composed of well interconnected mesopores and numerous micropores. Chemical analysis shows that the PCNTs contain sulfide and sulfone groups. When assessed as electrodes by a three-electrode system in 6 M KOH aqueous solution, the PCNTs displayed the excellent electrochemical performance. An optimal sample of PCNTs activated at 650 °C for 3 h not only exhibits a high specific capacitance of 331 F g −1 at 1 A g −1, but also shows considerable rate capability with the retention of 80.4% at 20 A g −1 . Additionally, it has the good cycling performance with 84% capacitance retention, while a high capability of about 243 F g −1 still reaches over 5000 cycles at 5 A g −1 . We presented a promising route to scale-up synthesize porous carbon nanotube electrode materials for high-performance supercapacitors. Graphical abstract: Porous carbon nanotubes (PCNTs) containing sulfur were successfully fabricated through a simple approach, which is the simultaneous activation and carbonization of sulfonated polydivinylbenzene nanotubes with KOH. The PCNTs take on hierarchical porous structure composed of well interconnected mesopores and numerous micropores. It is a promising route to scale-up synthesize porous carbon nanotube electrode materials for high-performance supercapacitors.